Prosperity in a changing world: Structural change and economic growth - Vera Demary; Michael Grömling; Galina Kolev; Jürgen Matthes (Institut der deutschen Wirtschaft (IW), 2016)
Structural change is both a challenge and an opportunity for countries and companies. However, there is no silver bullet in terms of superior economic models. Instead, different economic models can deal with structural change in a successful way. Both economies with a focus on services and those with a high share of manufacturing are able to achieve a high degree of economic growth and prosperity. Success factors are related to a solid performance with regard to the key drivers of structural change: globalisation, interconnectedness, innovation and knowledge as well as the economic framework. Economic policy - also at the EU level - should support companies and economies in reaping these potential benefits: fostering open and flexible markets as well as supporting European value chains and an intensification of knowledge in the production of goods and services are key success factors in this respect.
Keywords: F43; L16; O14; O43; 330